The NMDA receptor regulates integrin activation, ATP release and arterial thrombosis through store-operated Ca2+ entry in platelets - Reusswig, Friedrich; Yilmaz, Münteha; Brechtenkamp, Marius; Krueger, Irena; Metz, Lisa Maria; Klöcker, Nikolaj; Lammert, Eckhard; Elvers, Margitta (Frontiers in Cardiovascular Medicine, 2023)
Introduction Platelet activation and thrombus formation is crucial for hemostasis, but also trigger arterial thrombosis. Calcium mobilization plays an important role in platelet activation, because many cellular processes depend on the level of intracellular Ca2+ ([Ca2+](i)), such as integrin activation, degranulation, cytoskeletal reorganization. Different modulators of Ca2+ signaling have been implied, such as STIM1, Orai1, CyPA, SGK1, etc. Also, the N-methyl-D-aspartate receptor (NMDAR) was identified to contribute to Ca2+ signaling in platelets. However, the role of the NMDAR in thrombus formation is not well defined. Methods In vitro and in vivo analysis of platelet-specific NMDAR knock-out mice. Results In this study, we analyzed Grin1fl/fl-Pf4-Cre+ mice with a platelet-specific knock-out of the essential GluN1 subunit of the NMDAR. We found reduced store-operated Ca2+ entry (SOCE), but unaltered store release in GluN1-deficient platelets. Defective SOCE resulted in reduced Src and PKC substrate phosphorylation following stimulation of glycoprotein (GP)VI or the thrombin receptor PAR4 followed by decreased integrin activation but unaltered degranulation. Consequently, thrombus formation on collagen under flow conditions was reduced ex vivo, and Grin1fl/fl-Pf4-Cre+ mice were protected against arterial thrombosis. Results from human platelets treated with the NMDAR antagonist MK-801 revealed a crucial role of the NMDAR in integrin activation and Ca2+ homeostasis in human platelets as well. Conclusion NMDAR signaling is important for SOCE in platelets and contributes to platelet activation and arterial thrombosis. Thus, the NMDAR represents a novel target for anti-platelet therapy in cardiovascular disease (CVD).